“Mere Matter:” Causality, Subjectivity and Aesthetic Form in Erasmus Darwin - Dushane, Allison (Romanticism and Victorianism on the Net, 2009)
In his two-part medical treatise Zoonomia (1794-1796), Erasmus Darwin—physician, scientist, popular poet and grandfather of Charles Darwin—begins with a conception of living matter in order to envision an organic system of nature, in which the individual and the environment are not only interdependent, but also reciprocally determining. This essay contextualizes Darwin’s materialism within a wider debate over the status of “mere matter” in the Romantic era through a reading of section 39 of Zoonomia, “Of Generation,” alongside David Hartley’s psychological theories and Joseph Priestley’s thinking on the nature of matter. I argue that the perceived threat of materialism lies in the ways in which these systems of thought rethink the operation of causality, reorient conceptions of teleology, and thus rewrite the nature of the relationship between the human subject and material nature. A reading of the critical contemporary reactions to Darwin’s popular poetry further suggests that the same shifting conceptions of teleology, causality, and subjectivity drive Romantic era revolutions in aesthetic form.